Wartość sztuki a jej postrzeganie/odczuwanie przez młodzież - Wilk, Teresa (The value of art and its perception/feeling by young people, 2024)
This text is an attempt to show the value of art in the overall upbringing and education of the young generation and its perception by young people. Over the past years, cultural offers have been very diverse, but always to some extent addressed to young people. The aim of the study is to draw attention to the young generation’s interest in art and to recognize its value. The perception/feeling of art is an essential element of education and upbringing, preparing the young generation to realize their own aspirations and social duties on a daily basis. It is necessary to promote and educate the young generation in the belief that art enriches people in all areas of their activity. Experiencing art makes life fuller and better.